Prenatal Diagnosis of β Thalassaemia Tazeen Anwar*, - Tazeen Anwar , Nadeem Ikram , Tahira Zafar (Journal of Rawalpindi Medical College, 2014)
Background: To study the effectiveness of choronic villous sampling, followed by molecular analysis, for prenatal diagnosis of β thalassaemia Methods: In this descriptive study 116 high risk mothers with 12-16 weeks of pregnancy, underwent choronic villous sampling (CVS) for studying β thalassaemia mutations in fetuses. CVS sampling was done with a trans-abdominal route, under local anaesthesia and ultrasound guidance. The choronic villi extracted were investigated upon using genomic amplification of β globin gene by amplification refectory mutation system (ARMS). The couples were informed about the consequences and were advised to act accordingly Results: Chorionic villous sampling was advised to 161 and was done in 116 (72.04%) and 41 (25.46%) refused to proceed. Age of mothers ranged from 18 to 35 years. Nine (7.75%) were primrigravida. Consanguineous marriage were found in 85.34% couples. Majority (86.2%) previously had a child affected with β –thalassaemia major. On polymerase chain reaction , out of 116, 30.17% fetuses were diagnosed as beta thalassaemia major, having mutation of both alleles of β globin gene. One case (0.86%) had unidentified mutation. Frame shift 8-9 was the commonest mutation (42.85%), followed by IVS 1-5 (25.71%). cap+1 mutation was seen in 2.85%. Majority (94.3%) of the couples with β thalassaemia decided to abort. Spontaneous abortion, after the procedure, was found in one case . Conclusion: Ultrasound guided trans-abdominal CVS, with molecular assessment , is an effective procedure for prenatal diagnosis of β thalassaemia